Robobug: an autonomous mobile robot using microcontroller / Muhammad Suhaimi Sulong ... [et al.] - Sulong, Muhammad Suhaimi; Azman, Azali; Mohd Faiz, Nur Sofurah; Mohamed, Maziana (2008)
Some of the created robots had been rebuilt again to improve their ability and new research been made to get new ideas of creating higher technology robots. In this paper, writers described the development of mobile robot called RoboBug (Robot Bug) with three-legged that works automatically using 16F84 PIC microcontroller. The implementation of this project is separated into three main sections; they are mechanical, electrical and programming section. Six servo motors had been used with each leg consists of two servo motors and two infrared sensors act like feelers were used to avoid obstacle. The walking gait used a crawling concept with four basic movements; forward. backward, left and right. The results indicate that the robot has good stability of its body structure, good in avoiding obstacle and good in motion system. It is said to be the first step of developing a robot that really acts like a bug.